Feedback systems in multi-dose dry powder inhalers - Emeryk, Andrzej; Janeczek, Kamil (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
Dry powder inhalers (DPIs) are a large, highly diverse group of inhalation devices. DPIs differentiate the process of measuring the dose of the drug and preparing the inhaler for use, but also the way of transmitting and the scope of feedback on the inhalation process that the user receives. The functioning of simple and technologically advanced systems of feedback on the inhalation process in the most commonly used multi-dose DPIs is discussed. All these DPIs have a dose counter. Only three DPIs – Novolizer ® , Genuair ® and NEXThaler ® provide feedback to the patient in the form of auditory and visual signals confirming the correctness of the inhalation performed. This is important for the correct use of the inhaler, and thus for obtaining the expected therapeutic effects.